2019
DOI: 10.1080/14678802.2019.1561633
|View full text |Cite
|
Sign up to set email alerts
|

CSR and social conflict in the Brazilian extractive sector

Abstract: Corporate social responsibility (CSR) is an important means to address conflicts, support local development and build trust between businesses and civil society. Yet CSR often fails to live up to its ambitions and can even exacerbate conflicts between companies and communities. In this article we consider how changing CSR strategies over the past four decades between Brazilian company Vale to Norwegian company Hydro have fomented or mitigated company-community conflicts in Northern Brazil. We find that paterna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Hence, the citation network analysis found that economic “(I5) Insensitivity” occurred mostly when corporate DCSR efforts confronted underdeveloped or incorrigible domestic National Business Systems (NBSs). For example, Haque and Azmat (2015, p. 166)’s case study found that the institutional voids in developing contexts tarnish globalization because of their persistent “non‐compliance of CSR in labor‐intensive industries.” Similar patterns presented themselves in Latin America’s contexts where “forward‐thinking CSR approaches are vulnerable to failure where they prioritize business risk over community engagement, neglect to account for past legacies in areas of operation, and fail to create a shared vision of future development” (Hoelscher & Rustad, 2019, p. 99). The African context also harbored this inhibitory “(I5) Insensitivity” to weak regulation and unfettered institutional voids.…”
Section: Results: Diagnostic Presentation and Discussionmentioning
confidence: 76%
“…Hence, the citation network analysis found that economic “(I5) Insensitivity” occurred mostly when corporate DCSR efforts confronted underdeveloped or incorrigible domestic National Business Systems (NBSs). For example, Haque and Azmat (2015, p. 166)’s case study found that the institutional voids in developing contexts tarnish globalization because of their persistent “non‐compliance of CSR in labor‐intensive industries.” Similar patterns presented themselves in Latin America’s contexts where “forward‐thinking CSR approaches are vulnerable to failure where they prioritize business risk over community engagement, neglect to account for past legacies in areas of operation, and fail to create a shared vision of future development” (Hoelscher & Rustad, 2019, p. 99). The African context also harbored this inhibitory “(I5) Insensitivity” to weak regulation and unfettered institutional voids.…”
Section: Results: Diagnostic Presentation and Discussionmentioning
confidence: 76%
“…La imagen es la construcción mental de un público acerca de una marca, empresa, industria, sector o país, a partir de la evaluación de la información de ciertos atributos con los que se definen y diferencian las organizaciones (Capriotti, 2013); es decir, la imagen es una idea o actitud generada por el receptor de la información. En los 1970s, en medio de la crisis económica mundial, los esfuerzos corporativos se concentraron en mejorar la imagen y reputación de la empresa para lograr legitimidad social (Said et al, 2022), incorporándose cada vez más acciones de responsabilidad social y convirtiéndola de un imperativo para el éxito empresarial (Hoelscher & Rustad, 2019).…”
Section: La Imagen En El Sector Minerounclassified
“…In Brazil, environmental and human rights norms have begun to creep into the core businesses of many companies (Raufflet and Amaral, 2007), particularly multinationals with a brand name to protect, as acquiring a bad reputation might lead to consumer boycotts or negative NGO-led campaigns (Rueda et al., 2017). Thus, NGOs have emerged as important collective actors (Anholon et al., 2016) and coordinators of local multi-stakeholder dialogue projects (Hoelscher and Rustad, 2019). Therefore, the following hypothesis is proposed:H5: There is a positive association between the perception of pressure from NGOs and the extension of CSR practices.Customers today demand products and services with socially responsible attributes and may base their choices on socio-political judgments, thus influencing companies (Rothenhoefer, 2019; Zerbini, 2017).…”
Section: Theoretical Perspectives and Development Of Hypothesesmentioning
confidence: 99%